The existence of global weak solutions for a weakly dissipative Camassa-Holm equation in H1(R) - Lai, S.; Li, N.; Wu, Yong Hong (SpringerOpen, 2013)
The existence of global weak solutions to the Cauchy problem for a weakly dissipative Camassa-Holm equation is established in the space C([0,∞)×R)nL∞([0,∞);H1(R)) under the assumption that the initial value u 0 (x) only belongs to the space H 1 (R) . The limit of viscous approximations, a one-sided super bound estimate and a space-time higher-norm estimate for the equation are established to prove the existence of the global weak solution.